PENGARUH KUALITAS PELAYANAN DAN TARIF TERHADAP LOYALITAS PASIEN MELALUI KEPUASAN PASIEN (Studi Kasus Pada Rumah Sakit Banyumanik Semarang) - Zulfikar Akbar Sulistya; Sri Suryoko (Universitas Diponegoro, 2019)
The more rapid development of science and technology in the business world led to an increasingly tight competition and forcing businesses to be able to follow the competition in order to stay afloat and grow in running a business certain. This research was conducted at RS Banyumanik. From the interview against how many patients the known existence of Banyumanik RS complaints against rates and quality are given. As a company engaged in the field of services, the HOSPITAL must provide Banyumanik good service towards its customers, balanced with the rates according to what provided by RS Banyumanik.This research aims to know the influence of quality of service (X1) and rates (X2) against patient loyalty (Y) through patient satisfaction at RS Banyumnaik. Type of research uses explanatory research withdata collection method using interviews and data collection tools using questionnaires with a sample of 100 respondents RS patients Banyumanaik using a Non Probability method Sampling with the terms specified. Analysis techniques using the test validity, reliability testing, simple linear regression, multiple linear regression, t-test, F-test and SPSS tool with sobel test 23.From the results of the study showed that the quality of service effect strong enough against the patient's satisfaction of 33.4%, comparable to rates in effect strong enough against the patient's satisfaction of 25.6%. So the known quality of service to the satisfaction of the patients have a greater influence on compare rates. Whereas with the quality of service effect strong enough against patient loyalty of 31.5%. While tariff effect on patient loyalty of 18.5%. So the known quality of service to the loyalty of patients has a greater influence on compare rates.Advice that can be given to increase the loyalty of the patient that is improving the quality of Hospital services, such as Banyumanaik provide good air circulation, medical and non-medical personnel is fast and responsive, giving attention to all patients without choice, medical and non-medical personnel more friendly and polite towards patients.